Manipulating target size influences perceptions of success when learning a dart-throwing skill but does not impact retention - Ong, Nicole T.; Lohse, Keith R.; Hodges, Nicola J. (Frontiers in Psychology, 2015)
Positive feedback or experiences of success during skill acquisition have been shown to benefit motor skill learning. In this study, our aim was to manipulate learners’ success perceptions through a minor adjustment to goal criterion (target size) in a dart-throwing task. Two groups of novice participants practiced throwing at a large (easy) or a small (difficult) target from the same distance. In reference to the origin/centre of the target, the practice targets were alike in objective difficulty and indeed participants in both groups were not different in their objective practice performance (i.e. radial error from the centre). Although the groups experienced markedly different success rates, with the large target group experiencing more hits and reporting greater confidence (or self-efficacy) than the small target group, these practice effects were not carried into longer-term retention, which was assessed after a one-week delay. For success perceptions to moderate or benefit motor learning, we argue that unambiguous indicators of positive performance are necessary, especially for tasks where intrinsic feedback about objective error is salient.